1996
DOI: 10.7326/0003-4819-124-1_part_1-199601010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Genotype Analysis in Patients with Type II Mixed Cryoglobulinemia

Abstract: Mixed cryoglobulinemia may be related, at least in part, to the HCV genotype infecting the host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
5
5

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(82 citation statements)
references
References 0 publications
2
70
5
5
Order By: Relevance
“…This confirms the findings of Zignego et al, 30 who observed a higher prevalence of genotype 2a among cryoglobulinemic patients without symptomatic liver disease than among those with chronic hepatitis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This confirms the findings of Zignego et al, 30 who observed a higher prevalence of genotype 2a among cryoglobulinemic patients without symptomatic liver disease than among those with chronic hepatitis.…”
Section: Discussionsupporting
confidence: 91%
“…Apart from Mazzaro et al, 34 who reported a higher prevalence of genotype 1b (70.2%), among the other 138 patients reported 57 (41.3%) were bearing genotype 2a/2ac and 56 (40.5%) genotype 1b, confirming our findings. In particular, this was observed among patients with B cell NHL complicating MC, 6 among patients with MC, 30 a lymphoproliferative disorder which is currently considered an expression of low-grade B cell NHL, 8 among patients with monoclonal gammopathies, 31,42 and among patients with B cell NHL complicating MC or arising 'de novo' (Refs 43, 44 and the present report). Moreover, genotype 2a was recently found in a high percentage of Italian patients with autoimmune hepatitis.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…27,28 In serum samples, HCV genotyping was also performed using the Line Probe assay (INNO LiPA, Innogenetics, Gent, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic HCV infection has been associated with a variety of extrahepatic complications such as essential mixed cryoglobulinemia [9][10][11] , porphyria www.wjgnet.com…”
Section: Introductionmentioning
confidence: 99%